Role Ambiguity and Organizational Justice as the Predictors of Unethical Behavior Among Nurses - Dare Azeez Fagbenro (Journal of Client-centered Nursing Care, 2019)
Background: Unethical behavior among nurses is gradually becoming a severe problem in the health sector of Nigeria, and this calls for urgent concern. However, it may be associated with issues inside healthcare organizations. Therefore, this study aimed to investigate the relationship between role ambiguity, organizational justice, and unethical behavior among nurses. Methods: This was a cross-sectional study. In total, 300 participants were selected from Lagos State Teaching Hospital (LUTH) in Lagos metropolis using a convenience random sampling method. A structured questionnaire consisting of demographics and Unethical Behavior Scale (UBS), Role Ambiguity Scale (RAS), and Organizational Justice Scale (OJS) was used to collect the required data. Multiple regression model was used to analyze the obtained data in SPSS. Results: Among the subjects, 71.9% were females, and 28.1% were 99 males. Their age ranged from 24 to 57 years Mean±SD: 31.66±3.13. There was an independent relationship between role ambiguity and unethical behavior (β=0.229; t=3.157; P<0.05). Additionally, there was an independent relationship between organizational justice and unethical behavior (β=-0.317; t= -2.182; P<0.05). Conclusion: Role ambiguity and organizational justice predicted unethical behavior. Therefore, the authorities and hospital managers of Nigeria should design an intervention program tailored for resolving role ambiguity and improving organizational justice. This will help to reduce the menace of unethical behavior among these nurses.